Tasawuf Abd Al-Rahman Al-Sulamī (Perspektif Historis) - Muh Sofiudin (UIN Sunan Kalijaga Yogyakarta, 2018)
Abu Abd al-Rahman Al-Sulamī (d. 412 H) is known as a great Sufi scholar. In the realm of tasawuf, he formulated tasawuf as in al-muqaddimah fi al-tasawwuf and wrote the biographies of the Sufi scholars in his book Thabaqat al-Sufiyyah. The tasawuf review in the form of biography of the Sufi ulama gives a distinctive picture in the process of formulating the concept of tasawuf. On the other hand, although al-Sulamī is known as a tasawuf briliant thinker, in Indonesia, it turns out to be less prestige than his pupil named al-Qusyairi. In fact, al-Sulamī is al-Qusyairi’s teacher who actually has more scientific authority than his pupil. This fact can be caused by many factors, one of which is the lack of information and references to al-Sulamī.